Bike mobilities, democratic revival and the local fix - Nacima Baron (Belgeo)
This article explores the local political strategies associated with the implementation of sustainable bike policies in southern European cities. It combines geographical concepts and methods , on the one hand, and sustainable policy studies on the other hand, with the aim of highlighting the specificities of the Mediterranean political context of mobility transition. Using Valencia as a case study, it shows that tactical urbanism is being used to put sustainable mobilities on the local agenda. This justifies and embodies a change in municipal policy and politics after a decade of crisis. Sustainable mobility projects materialise and spatialise, in various ways, democratic values within public space. The article therefore studies the strategies employed to mark the urban territory with green mobility infrastructures (part 1); it reveals the construction of a discursive space that polarises local debates (part 2); it describes the symbolic reintegration of Valencia into a network of model cities (part 3). Such a strategy does not create an effective Mediterranean model of the cycle-friendly city, because it does not modify the structural organisation of space or the social representations that underpin current mobility practices (part 4).